Efficacy of Solvent Type on Antioxidant Activity of Artocarpus heterophyllus Leaves Extract: A Scoping Review - Ida Bagus Ideyogiswara; Bagus Komang Satriyasa; Agung Nova Mahendra; Agung Wiwiek Indrayani; Ketut Agus Adrianta (GLOBAL HEALTH SCIENCE GROUP, 2026)
Jackfruit leaves (Artocarpus heterophyllus) contain various bioactive compounds that have the potential as natural antioxidants. The antioxidant activity of jackfruit leaf extract is influenced by the type of solvent used during the extraction process. Objective to identify the effectiveness of various types of solvents on the antioxidant activity of jackfruit leaf extract. This study used a scoping review method by reviewing articles from PubMed, ScienceDirect, and Google Scholar in 2020–2025 Searching strategy using the keywords